Investigation of bhv-1, bvdv and eblv infections in bulls selected for artificial investigation of bhv-1, bvdv and eblv infections in bulls selected for artificial - Orhan Yapkıç; Oya Bulut; Atilla Şimşek; Sibel Yavru; Mehmet Kale; OğuzhanAvcı (Eurasian Journal of Veterinary Sciences)
In this study, blood samples taken from 143 bulls choosen bulls that using in artificial insemination centers were investigated for antibodies against BHV-1, BVDV and EBLV infections by ELISA/Ab. It was determined as positive that antibodies against 12 bulls (8.3%) for BHV-1, 25 bulls (17.4%) for BVDV and 14 bulls (9.7%) for EBLV. Besides, all seronegative bulls were also detected as antigen negative by ELISA/Ag.